Long-term outcomes of Fontan palliation; the influence of the dominant ventricle - Abdelmonem M. Helal; Jameel Al-Ata; Nashwa Mostafa Badawy; Ahmed Abdelwahed; Wejdan Khaled Ba-Atiyah; Anhar Ali Baeshen; Abdullah J. Alata; Ahmed F. Elmahrouk; Mohammad S. Shihata; Ahmed A. Jamjoom; Samia Bekheet (The Cardiothoracic Surgeon)
Abstract Background Factors affecting the outcomes after Fontan palliation are still controversial. Thus, this study aimed to compare hospital and long-term outcomes after Fontan palliation in patients with left-dominant, right-dominant, and co-dominant ventricles. Moreover, the study sought to identify factors associated with long-term surgical reintervention, catheter-based interventions, and morality. This retrospective cohort study was conducted in a single tertiary referral center between 2010 and 2024 and included all patients who had Fontan palliation (n = 247). The patients were grouped according to the dominant ventricle into three groups: left-dominant (n = 105), right-dominant (n = 108), and codominant (n = 36). Results No significant differences were found in demographic variables among groups. Heterotaxy was more common in codominant patients who exhibited higher preoperative saturation levels. Early postoperative complications were more frequent in right-dominant patients, with low cardiac output significantly lower in left-dominant patients. Codominant patients experienced more arrhythmias and complete heart block, while operative mortality rates were similar across groups. During a median follow-up of 80 months, the freedom from surgical reintervention at 5, 10, and 15 years was highest in the left-dominant group (97%) compared to right dominance (93%, 78%) and codominance (97%, 87%). Mortality was significantly higher in the right-dominant and codominant groups, with survival rates at 5, 10, and 15 years being 97% for left dominance, 92% for right dominance, and 91% for codominance. Factors influencing long-term mortality were older age, right dominance, and elevated pulmonary artery pressure. Conclusions Patients with left dominance exhibited superior survival rates and fewer complications compared to those with right dominance and codominance. The findings emphasize the importance of anatomical considerations in risk stratification and clinical decision-making. Young age at the time of palliation could improve the outcomes of the Fontan procedure.